Comparative study of traditional and lab-scale roasting method for unpeeled robusta coffee in Bromo-Tengger-Semeru mountain slope regions - Fibrianto, Kiki; Ferrasta, Onky Audika; Bimo, Igoy Arya (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Traditionally, Robusta coffee is predominantly processed using the natural method. However, in certain regions, Robusta green beans are produced without removing their outer skin (pericarp) throughout the entire processing stages. This distinctive method is aimed at increasing yield, making the coffee more affordable for a broader consumer base. This study investigated the traditional production practices of Robusta coffee in three regions within the Bromo-Tengger-Semeru Mountains protected area: Benjor and Jabung in Malang Regency, and Wonorejo in Pasuruan Regency. The entire traditional green bean production process in these regions was observed and documented. Additionally, the roasting methods traditionally employed by farmers were compared to lab-scale medium-to-dark controlled roasting processes. A completely randomized block design was employed to evaluate the physical, chemical, and sensory quality of unpeeled Robusta coffee from Benjor, Jabung, and Wonorejo. The sensory quality was assessed using the Specialty Coffee Association of America (SCAA) official cupping test. The results showed that traditional practices in Benjor and Jabung produced coffee with a cupping score above 70, meeting the standards for good commodity-grade coffee. Interestingly, the coffee from Wonorejo, which initially had a lower sensory score, reached a comparable quality level when roasted under controlled lab-scale conditions. Gas chromatography-mass spectrometry (GC-MS) analysis further confirmed that lab-scale roasting enhanced sweet flavor notes compared to traditional farmer practices in Wonorejo.